A Cognitive Model for Meetings in the Software Development Process. Issue 1 (11th November 2011) - Misra, Sanjay; Akman, Ibrahim
Abstract Meetings are at the heart of the software development process (SDP) and can be of different types. The present article first proposes an abstract cognitive model for meetings, which represents how different types of meetings are affected by cognitive activities at different stages within the SDP. Second, and based on the analysis of meetings at different stages of SDP, it proposes the removal of such meetings from some of the stages within the program by using a cognitive evaluation model for meetings and their replacement, instead, with information and communication technology tools and techniques by means of a cognitive evaluation model. The abstract cognitive model and the evaluation model are validated empirically through experimentation, carried out through a detailed analysis of a target group composed of information technology professionals. © 2011 Wiley Periodicals, Inc.